Peran Guru Dalam Memfasilitasi Interaksi Sosial Anak Autis di Kelas - Yolandha, Mayang Rehza; Ivarianti, Krisna; Kamilla, Khairunnisa Nazwa; Alifia, Nayla Aura; Christina, Nova; Kartika, Wilda Isna; Pertiwi, Adharina Dian (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Disability includes a range of conditions that affect an individual’s ability to interact within society. In autistic children, difficulties in communication and social interaction are the primary challenges that affect classroom participation. This study explores the role of teachers in facilitating social interaction among autistic children in an early childhood education setting. Using a descriptive qualitative case study, data were collected through observations, interviews, and documentation. The analysis involved data reduction, data presentation, and verification. Findings show that the two autistic children observed still relied heavily on teacher support, with limited reciprocal interaction. Teachers acted as facilitators, motivators, mentors, and evaluators by providing structured guidance and emotional support. The novelty of this study lies in its focus on real classroom interactions in PAUD settings and the adaptive strategies teachers use based on the child’s autism severity. Practically, the study highlights the need for professional development for early childhood teachers in inclusive communication strategies and play-based social facilitation. Future research is recommended to explore alternative pedagogical approaches and collaborative models involving teachers, therapists, and parents.